Estratégias para adoção da inseminação artificial em vacas zebuínas - Magalhães, Priscila Cristina Martins (2013)
In search of economically viable biotechniques to improve reproductive efficiency in cattle breeding, this study aimed to evaluate the technical viability of the use of synchronization protocols after the first fixed-time artificial insemination (FTAI) and before the pregnancy diagnosis. In the first experiment, the FTAI followed by estrous detection was compared to conventional AI and to FTAI followed by resynchronization 21 days after FTAI; and to conventional IA. The same protocol was used for te groups that utilized FTAI, with the following chronology: day 0, insertion of progesterone intravaginal device and treatment with 2 mg of estradiol benzoate; day 8, removal of the device and injection of 500 mg of sodium cloprostenol and 1 mg of estradiol cypionate; day 10, FTAI. Twenty one days after FTAI, every cow in the resynchronization group received a intravaginal implant of 1 mg of estradiol benzoate. After pregnancy diagnosis, on day 28, the empty animals received 500 mg of sodium cloprostenol, 1 mg of estradiol cypionate and the implant was removed. FTAI was done on day 30. Conventional AI was performed 12 hours after estrous detection with the use of a teaser. It was observed that the conception rate did not differ with the treatments after the first service, neither did the pregnancy rate at the end of 90 days of breeding period. In the second experiment, the resynchronization protocol was compared to FTAI followed by natural mating in zebu cows, used in the production of F1 Holstein x Zebu females. The effect of the resynchronization on the pregnancy rate over 75 days of BP was not observed. The resynchronization was inefficient to induce cyclicity in cows in anoestrus after the first FTAI. The resynchronization, before the pregnancy diagnosis, must be used carefully, specially in situations where the estrous detection is low.